Improving Faculty Knowledge of Affirmative and Inclusive Health Care: An Applied Improvement Project - Stacie Klima (Teaching and Learning Excellence through Scholarship)
This intervention was designed to investigate the understanding and pedagogical application of affirmative and inclusive healthcare for transgender and gender non-conforming individuals by School of Health Profession (SHP) faculty. The intervention was a faculty workshop on affirmative and inclusive health care. Participants were recruited from the Community College of Baltimore County who teach specifically in the SHP. A total of 7 faculty participants attended both the workshop as well as the post-intervention individual interview. Guiding questions about the efficacy of the workshop and its potential lasting effects were utilized by the project manager to guide the study. Participant interviews were the primary source of qualitative data. Participant interviews were analyzed using in vivo coding and thematic analysis. Results indicated that the SHP faculty workshop on affirmative and inclusive healthcare improved participants’ knowledge of gender identity and affirming practices in healthcare and improved their understanding of how to apply this information to their course curriculum. The faculty workshop proved to be an effective tool for increasing the faculties’ understanding and pedagogical application of affirmative and inclusive healthcare. Implications for professional practice are to continue the implementation of the faculty training workshop.